Real-Time Data Processing with Cloud Technologies - Santhosh Kumar Rai, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Real-time data processing, empowered by cloud technologies, has revolutionized how businesses transform raw data streams into actionable insights. This transformative approach enables organizations to respond instantly to changing conditions, identify emerging opportunities and threats, and make decisions based on current information. The evolution from traditional batch processing to modern stream processing architectures represents a technical advancement and a fundamental shift in how enterprises conceptualize their relationship with data. By examining key components, implementation challenges, best practices, industry applications, and future trends, we explore how cloud-based real-time processing creates competitive advantages across diverse sectors while democratizing access to sophisticated data capabilities previously available only to resource-rich organizations.
Keywords: Cloud Computing; Data Ingestion; Edge Processing; Real-Time Analytics; Serverless Architecture